Analsis Implementasi Kebijakan Pemungutan Pajak Reklame Videotron Dalam Rangka Peningkatan Penerimaan Pajak Reklame Pada Unit Pelayanan Pemungutan Pajak Daerah Wilayah Menteng Jakarta Pusat Tahun 2021 - Muhamad Ridwan Rinaldi; Rahadi Pratomo Singgih (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Advertisement tax has become an interesting topic for study. Advertisements are widely used by various institutions, both business and non-business, to convey specific information. The development of businesses accompanied by rapid technological advancements makes the development of advertisements worth noting, especially from a taxation perspective which may be a promising source of revenue for local governments. One form of advertisement that is currently developing is the videotron type. Videotron is an electronic medium that displays videos using Light Emitting Diode (LED). LED is a type of lighting that uses semiconductors to convert electricity into light. It is usually used outdoors as a sign of a place or to display advertisements. The purpose of this research is to analyze the implementation of the videotron advertisement tax collection policy in order to increase advertisement tax revenue at the Regional Tax Collection Unit of Menteng, Central Jakarta in 2021, using a qualitative method where primary data is obtained through interviews and secondary data. The results of this analysis explain that the implementation of the videotron advertisement tax collection policy in order to increase advertisement tax revenue at the Regional Tax Collection Unit of Menteng, Central Jakarta in 2021 is categorized as good in terms of 4 (four) aspects, namely : 1) Communication, 2) Resources, 3) Disposition, and 4) Bureaucratic Structure, with a slight problem in the Resources aspect where the ratio of tax officers is still very small compared to the number of videotron advertisement tax objects.